The Effect of Various Poly (N-vinylpyrrolidone) (PVP) Polymers on the Crystallization of Flutamide - Dawid Heczko; Barbara Hachuła; Paulina Maksym; Kamil Kamiński; Andrzej Zięba; Luiza Orszulak; Marian Paluch; Ewa Kamińska (MDPI AG, 2022)
In this study, several experimental techniques were applied to probe thermal properties, molecular dynamics, crystallization kinetics and intermolecular interactions in binary mixtures (BMs) composed of flutamide (FL) and various poly(N-vinylpyrrolidone) (PVP) polymers, including a commercial product and, importantly, samples obtained from high-pressure syntheses, which differ in microstructure (defined by the tacticity of the macromolecule) from the commercial PVP. Differential Scanning Calorimetry (DSC) studies revealed a particularly large difference between the glass transition temperature (Tg) of FL+PVPsynth. mixtures with 10 and 30 wt% of the excipient. In the case of the FL+PVPcomm. system, this effect was significantly lower. Such unexpected findings for the former mixtures were strictly connected to the variation of the microstructure of the polymer. Moreover, combined DSC and dielectric measurements showed that the onset of FL crystallization is significantly suppressed in the BM composed of the synthesized polymers. Further non-isothermal DSC investigations carried out on various FL+10 wt% PVP mixtures revealed a slowing down of FL crystallization in all FL-based systems (the best inhibitor of this process was PVP Mn = 190 kg/mol). Our research indicated a significant contribution of the microstructure of the polymer on the physical stability of the pharmaceutical-an issue completely overlooked in the literature.